2017
DOI: 10.3847/1538-4357/aa5b8b
|View full text |Cite
|
Sign up to set email alerts
|

IRIS, Hinode, SDO, and RHESSI Observations of a White Light Flare Produced Directly by Non-thermal Electrons

Abstract: An X1.6 flare occurred in AR 12192 on 2014 October 22 at 14:02 UT and was observed by Hinode, IRIS, SDO, and RHESSI. We analyze a bright kernel which produces a white light (WL) flare with continuum enhancement and a hard X-ray (HXR) peak. Taking advantage of the spectroscopic observations of IRIS and Hinode/EIS, we measure the temporal variation of the plasma properties in the bright kernel in the chromosphere and corona. We found that explosive evaporation was observed when the WL emission occurred, even tho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
40
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 75 publications
10
40
0
1
Order By: Relevance
“…Further evidence for this process was reported by Kowalski et al (2017), who combined IRIS and RHESSI data with electron-beam-driven flare simulations and found that the NUV continuum intensity was consistent with hydrogen Balmer recombination radiation emitted in two separate atmospheric layers where the electron beams release their energy (see also Section 7). These findings appear to support the hypothesis that WLF emission is associated with energy deposition from non-thermal electrons streaming from the corona and propagating down towards the chromosphere (see also Lee et al, 2017). On the other hand, recent IRIS observations of a WLF, showing spectral features typical of UV bursts, such as enhanced and broadened Si IV and C II profiles superimposed by chromospheric absorption lines, combined with the lack of significant HXR flux in RHESSI, have also provided evidence for a different scenario, in which the WLF is caused by reconnection occurring locally in the lower atmosphere (Song et al, 2020).…”
Section: Iris Lines As Diagnostics Of Flare Heating Mechanismssupporting
confidence: 82%
“…Further evidence for this process was reported by Kowalski et al (2017), who combined IRIS and RHESSI data with electron-beam-driven flare simulations and found that the NUV continuum intensity was consistent with hydrogen Balmer recombination radiation emitted in two separate atmospheric layers where the electron beams release their energy (see also Section 7). These findings appear to support the hypothesis that WLF emission is associated with energy deposition from non-thermal electrons streaming from the corona and propagating down towards the chromosphere (see also Lee et al, 2017). On the other hand, recent IRIS observations of a WLF, showing spectral features typical of UV bursts, such as enhanced and broadened Si IV and C II profiles superimposed by chromospheric absorption lines, combined with the lack of significant HXR flux in RHESSI, have also provided evidence for a different scenario, in which the WLF is caused by reconnection occurring locally in the lower atmosphere (Song et al, 2020).…”
Section: Iris Lines As Diagnostics Of Flare Heating Mechanismssupporting
confidence: 82%
“…The macro velocities of the downward moving hydrodynamic shocks in the F10, F11 and F12 HYDRO2GEN models are similar to those in the models presented in Fisher et al (1985) for beams of electrons with equivalent parameters and can reach the values derived from observations by Lee et al (2017). This is essentially different from the work of Allred et al (2005), which uses the heating function by electrons beams derived by Emslie (1978) and Nagai & Emslie (1984) truncated in the top flaring atmosphere to keep a flaring corona not overheated (see Fisher et al (1985)) and at the upper chromospheric column depths just before the stopping depth of the electrons with lower cutoff energy to avoid the infinity problem (Mauas & Gómez 1997) (Kontar et al 2011, p6, footnote).…”
Section: Hydrodynamicssupporting
confidence: 74%
“…Instead, such currents have non-gyrotropic electron velocity distributions caused by the magnetic reconnection processes. These distributions may feature additional instabilities, within current sheets and when propagating into background plasma (Maneva et al, 2016), which would allow for a better understanding of (or new) onset mechanisms of solar eruptive events.…”
Section: Outlook For Solar Physicsmentioning
confidence: 99%